Micro- and mesoscale mechanical properties of an ultra-fine grained CrFeMnNi high entropy alloy produced by large strain machining - Gigax, Jonathan G.; El-Atwani, Osman; McCulloch, Quinn; Aytuna, Berk; Efe, Mert; Fensin, Saryu; Maloy, Stuart A.; Li, Nan (Scripta materialia, 2020)
Large strain machining (LSM), an attractive severe deformation technique due to its simplicity, has been previously used to produce a fine-grained structure in a variety of alloys. An equiatomic CrFeMnNi high entropy alloy was subject to various LSM conditions. The microstructure was observed to have ultra-fine grains in all conditions, with some more homogeneous than others. Nanoindentation showed a considerable increase in hardness for all LSM conditions with respect to the base material. Mesoscale tensile testing revealed that, while the tensile strength of the LSM specimens was higher than that of the base material, the ductility was reduced significantly. [Display omitted]